Dual Education and its Impact on developing Professional Skills: (A study on the impact of the work environment and practical training on female students’ personalities and job performance) - Ayat Abdeen; Sireen Ahmad Hoso; Mousa Alrefaya (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
This study investigates the impact of dual education on the development of professional skills, focusing on how the work environment and practical training influence female students’ personalities and job performance. Dual education, which integrates theoretical learning with hands-on workplace experience, has expanded notably in Europe over the past two decades, yet faces implementation challenges in certain regions. The research emphasizes the importance of practical training in enhancing students’ adaptability, problem-solving abilities, and employability, while addressing gender disparities within vocational sectors. Data were collected using semi-structured interviews and surveys from participants across diverse professional fields, with a balanced representation of males and females. Findings reveal a pronounced gender gap: women dominate sectors such as healthcare and education, whereas men predominate in engineering, IT, and construction. The study highlights that effective dual education requires strong collaboration between educational institutions and industry partners, supportive work environments, and targeted policies to address gender stereotypes and work-life balance challenges. Recommendations focus on improving dual education frameworks, developing pedagogical support for trainers, and fostering inclusive career pathways for female students. The research contributes to the ongoing discourse on vocational education reform by providing practical insights and policy implications to enhance skill development and gender equality in the workforce.